2012
DOI: 10.1111/j.1477-2574.2012.00506.x
|View full text |Cite|
|
Sign up to set email alerts
|

Advanced age is a risk factor for post-operative complications and mortality after a pancreaticoduodenectomy: a meta-analysis and systematic review

Abstract: There is an increased incidence of post-operative mortality and pneumonia after a PD among all elderly patients ≥75 years of age, as well as an increased incidence of post-operative complications among patients ≥80 years of age. Additional randomized control trials studying post-PD operative outcomes in elderly vs. younger patients with standardization of comorbidities is therefore necessary to confirm the conclusions presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(48 citation statements)
references
References 19 publications
1
41
2
4
Order By: Relevance
“…These considerations are accentuated, as the elderly population is steadily growing and age remains an established risk factor for postoperative complications and mortality. 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…These considerations are accentuated, as the elderly population is steadily growing and age remains an established risk factor for postoperative complications and mortality. 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Age limits are being pushed for various other types of major operations, such as oesophageal and pancreatic surgery, partly because of an increasing health status of the elderly [34-36]. Similarly, an increasing number of elderly patients with good performance status can be considered for hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable discussion in published literature regarding outcomes in elderly is currently underway. The published data is inconsistent as a result of differences in age groups under comparison [11]. Some authors have reported acceptable morbidity and mortality rates after a pancreatoduodenectomy (PD) in octogenarians [8].…”
Section: Discussionmentioning
confidence: 99%
“…Some papers demonstrate that octogenarians might undergo surgery without a significant increase of morbidity rates related to comorbidities such as cardiac or pulmonary diseases [18]. Nevertheless, the potential for non-surgical complications as well as the increased risk of perioperative mortality, which was obvious in our series, should be assessed and taken into account [8,11]. These risks are commonly associated with polypharmacy, cardiac and pulmonary diseases, poor nutritional status requiring intensive perioperative support and monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation